Polyunsaturated Fatty Acids, Exercise, and Cancer-Related Fatigue in Breast Cancer Survivors - Matsuoka, Yutaka; Tsuji, Katsunori; Ochi, Eisuke (Frontiers in Physiology, 2021)
Cancer-related fatigue (CRF) is one of the most frequently reported and disabling symptom in cancer survivors. With its negative impact on activities of daily living, work, social activities, and mood, CRF causes severe impairment of quality of life. Previous study showed that omega-6 polyunsaturated fatty acids (PUFA) supplementation unexpectedly reduced Cancer Fatigue Scale (CFS) compared with omega-3 PUFA supplementation and omega-6 PUFA supplementation reduced pro-inflammatory serum markers in fatigued American breast cancer survivors. Meanwhile, a recent meta-analysis of individual patient data revealed significant benefits of exercise interventions on CRF. Recently, we completed our randomized controlled trial among early stage Japanese breast cancer survivors, we examined the effect of baseline blood PUFA characteristics on change in CRF during the 12-week trial by exercise group and confirmed that increased CFS was associated with both docosahexaenoic acid p =0.06) and omega-3 index (p =0.08) at baseline in all participants (n = 46, omega-6/omega-3 ratio = 6.79, SD = 1.90). Contrary, docosahexaenoic acid (DHA) at baseline was positively correlated with change in CRF (r = 0.40, p =0.06) in control group (n=24, omega-6/omega-3 ratio = 7.0). Moreover, eicosapentaenoic acid (EPA) at baseline was positively correlated with leg strength (r = 0.39, p =0.10) in exercise group. In conclusion, Blood PUFA balance might be associated with the effect of exercise on CRF. In addition, higher EPA in individuals who conducted exercise likely has beneficial effect on muscle strength. Further investigation is needed to clarify the interaction between PUFA and exercise for alleviating CRF.